Bismuth-based catalyst as well as preparation method and application thereof

The reversible bismuth-based catalyst prepared by solvothermal reaction and calcination solves the problem of structural changes in the electrochemical carbon dioxide reduction process of bismuth-based catalysts, and achieves high efficiency reduction and high formic acid selectivity within a wide voltage range, with good industrial application prospects.

CN119954203APending Publication Date: 2025-05-09UNIV OF MACAU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510113710.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

Existing bismuth-based catalysts are prone to reducing reconstruction during electrochemical carbon dioxide reduction, resulting in changes in catalyst structure and collapse, and it is difficult to maintain high selectivity over a wide voltage range.

Method used

By mixing bismuth nitrate, ammonia water, ethylene glycol and benzyl alcohol for solvothermal reaction, a basic bismuth nitrate precursor was obtained, and the temperature was controlled to be less than 190°C during the calcination process, a bismuth-based catalyst with variable chemical composition and reversible reversible was prepared. The catalyst exhibits a bismuth oxygen carbonate structure at a low applied voltage, a bismuth metal structure at a high applied voltage, and spontaneously reconstituted into bismuth oxygen carbonate after the voltage is removed.

Benefits of technology

It realizes efficient electrochemical carbon dioxide reduction of bismuth-based catalysts within a wide voltage range, improves the selectivity of formic acid and the conversion Faraday efficiency, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954203A_ABST
    Figure CN119954203A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth-based catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysis. The preparation method of the bismuth-based catalyst provided by the invention comprises the following steps: mixing bismuth nitrate, ammonia water, ethylene glycol and benzyl alcohol, and carrying out solvothermal reaction to obtain a basic bismuth nitrate precursor; and calcining the basic bismuth nitrate precursor to obtain the bismuth-based catalyst, the calcining temperature is less than 190 DEG C. The bismuth-based catalyst is prepared by adopting specific raw materials and specific preparation conditions, ammonia water can be complexed with bismuth nitrate, solvothermal reaction can be carried out in a specific alcohol solvent, the unique bismuth-based catalyst can be synthesized, and the bismuth-based catalyst has the characteristics of variable and reversible chemical composition, and is suitable for industrial production. Therefore, electrochemical carbon dioxide reduction can be realized in a relatively wide voltage range, and the method has a good application prospect in industrial large-scale electrochemical carbon dioxide reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalysis technology, and in particular relates to a bismuth-based catalyst and a preparation method and application thereof. Background Art

[0002] In the context of increasingly serious global climate change, environmental issues such as ozone layer depletion and global warming have attracted more and more attention. Carbon dioxide (CO2) is one of the main greenhouse gases. Its emission not only exacerbates the greenhouse effect, but also poses a serious threat to human health and ecosystems. Therefore, reducing CO2 emissions and developing sustainable clean energy technologies have become one of the current problems that need to be solved urgently. Electrochemical carbon dioxide reduction (ECR), as a green and low-carbon technology, is generally considered to be one of the important ways to achieve CO2 emission reduction and efficient utilization of CO2 resources. By applying voltage in the electrolytic cell, CO2 can be reduced to high value-added compounds (such as formic acid, carbon monoxide, formaldehyde, methane, etc.), which can realize the resource utilization of CO2 and reduce the use of fossil fuels. In addition, ECR can also effectively reduce greenhouse gas emissions and improve energy utilization, which is particularly important for promoting clean energy technology and sustainable development.

[0003] However, the industrial application of ECR ​​still faces a series of challenges, such as low CO2 reduction efficiency, poor product selectivity, and unstable electrocatalyst activity. Bismuth-based catalysts are considered to be an efficient catalyst for converting CO2 into formic acid through ECR. They have high selectivity for formic acid, and bismuth itself is inexpensive, non-toxic and harmless, making it a catalyst with great prospects for industrial application. However, although bismuth-based catalysts have high selectivity for formic acid, the electrochemical hydrogen evolution reaction (HER) and ECR are competing reactions, and the two reactions are prone to proceed simultaneously at the same potential, resulting in a reduction in ECR product selectivity. Therefore, it is one of the difficult problems in the industry to maintain the high selectivity of bismuth-based catalysts over a wider voltage range. On the other hand, since ECR is a reduction reaction, bismuth-based catalysts are very likely to undergo reductive reconstruction into metallic bismuth during the ECR process, resulting in changes and collapse of the pre-designed catalyst structure. If the reconstruction of bismuth-based catalysts during the ECR process is controlled, it is another difficult problem in the industry. Summary of the invention

[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a method for preparing a bismuth-based catalyst, by which a bismuth-based catalyst with a variable and reversible chemical composition can be prepared, which can especially realize electrochemical carbon dioxide reduction within a wider voltage range.

[0005] A second object of the present invention is to provide a bismuth-based catalyst prepared by the above preparation method.

[0006] A third object of the present invention is to provide an application of the above-mentioned bismuth-based catalyst in electrochemical carbon dioxide reduction.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a method for preparing a bismuth-based catalyst, comprising the following steps: mixing bismuth nitrate, ammonia water, ethylene glycol and benzyl alcohol, and performing a solvent thermal reaction to obtain a basic bismuth nitrate precursor; calcining the basic bismuth nitrate precursor to obtain the bismuth-based catalyst; the calcination temperature is less than 190°C.

[0009] Preferably, the usage ratio of the bismuth nitrate to the ammonia water is 1 g: (5-20) mL; more preferably, it is 1 g: (8-15) mL.

[0010] Preferably, the usage ratio of the bismuth nitrate to the ethylene glycol is 1 g: (200-800) mL; more preferably, 1 g: (300-600) mL.

[0011] Preferably, the usage ratio of the bismuth nitrate to the benzyl alcohol is 1 g: (200-800) mL; more preferably, 1 g: (300-600) mL.

[0012] Preferably, the volume ratio of the ethylene glycol to the benzyl alcohol is 1:(0.5-2); more preferably, it is 1:(0.8-1.5).

[0013] Preferably, the temperature of the solvothermal reaction is 100 to 180°C; more preferably, 120 to 160°C.

[0014] Preferably, the solvent thermal reaction time is 10 to 40 hours; more preferably, it is 16 to 32 hours.

[0015] Preferably, the calcination temperature is 50-180°C; more preferably 80-170°C; more preferably 90-150°C; for example, it can be any one of 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C or a range between any two of them, such as 100-140°C.

[0016] Preferably, the calcination time is 3 to 7 hours; more preferably, it is 4 to 6 hours.

[0017] Preferably, the calcination is performed under air atmosphere.

[0018] Preferably, after the calcination, the method further comprises the following steps: subjecting the calcined product obtained by the calcination to an electrochemical reduction reaction with a solution containing carbon dioxide under an applied voltage to obtain the bismuth-based catalyst.

[0019] Preferably, the magnitude of the applied voltage is 0.2 to 2V; more preferably, it is 0.7 to 1.2V.

[0020] In the present invention, the applied voltage is a voltage relative to the reversible hydrogen electrode.

[0021] Preferably, the time for applying the voltage is 1 to 5 hours; more preferably, it is 2 to 4 hours.

[0022] Under the condition of applied voltage, the calcined product reacts with a solution containing carbon dioxide, and a change in chemical composition can occur. Under low applied voltage, the calcined product can be transformed from basic bismuth nitrate to bismuth oxycarbonate; further increasing the applied voltage, under high applied voltage, bismuth oxycarbonate is transformed into elemental bismuth; removing the applied voltage, the metallic bismuth continues to react with the solution containing carbon dioxide and is transformed back into bismuth oxycarbonate.

[0023] The second aspect of the present invention provides a bismuth-based catalyst prepared by the preparation method described in the first aspect of the present invention.

[0024] Preferably, the chemical composition of the bismuth-based catalyst changes with different applied voltages in a solution containing carbon dioxide; at low applied voltage or no applied voltage, the chemical composition of the bismuth-based catalyst is basic bismuth nitrate or bismuth oxycarbonate; at high applied voltage, the chemical composition of the bismuth-based catalyst is elemental bismuth.

[0025] Preferably, the low applied voltage has a magnitude range of greater than 0V and less than or equal to 0.9V; the high applied voltage has a magnitude range of greater than 0.9V and less than or equal to 2V.

[0026] Preferably, the solution containing carbon dioxide is a saturated solution of carbon dioxide.

[0027] Preferably, the solution containing carbon dioxide further contains bicarbonate, such as potassium bicarbonate, sodium bicarbonate, etc.; in the solution containing carbon dioxide, the concentration of bicarbonate may be 0.1 to 1 mol / L; more specifically, it may be 0.3 to 0.7 mol / L.

[0028] In some embodiments of the present invention, the elemental bismuth formed under a high applied voltage continues to react in a solution containing carbon dioxide to form bismuth oxycarbonate after the applied voltage is removed; specifically, the continued reaction time is greater than or equal to 5 minutes.

[0029] The third aspect of the present invention provides a use of the bismuth-based catalyst described in the second aspect of the present invention in electrochemical carbon dioxide reduction (ECR).

[0030] Preferably, the application is the application of the bismuth-based catalyst in the electrochemical reduction of carbon dioxide to produce formic acid.

[0031] The bismuth-based catalyst provided by the invention has a good catalytic effect on the electrochemical carbon dioxide reduction (ECR) reaction, and in particular has a high formic acid selectivity.

[0032] The beneficial effects of the present invention are as follows: a bismuth-based catalyst is prepared by adopting specific raw materials and specific preparation conditions, wherein ammonia water can be complexed with bismuth nitrate to allow it to undergo a solvothermal reaction in a specific alcohol solvent, thereby being able to synthesize the unique bismuth-based catalyst of the present invention, which has the characteristics of variable and reversible chemical composition, and can thus achieve electrochemical carbon dioxide reduction within a wider voltage range, and has good application prospects in industrial large-scale electrochemical carbon dioxide reduction.

[0033] Specifically, compared with the prior art, the present invention also has the following advantages:

[0034] Since the electrochemical carbon dioxide reduction reaction and the electrochemical hydrogen evolution reaction are competitive reactions, the key to realizing large-scale application of materials is to suppress the electrochemical hydrogen evolution reaction while realizing efficient electrochemical carbon dioxide reduction reaction in a wide voltage range. The present invention prepares a basic bismuth nitrate precursor by a solvothermal method, and then applies different voltages to it during the electrochemical carbon dioxide reduction reaction to obtain a structurally reversible bismuth-based catalyst. This structurally reversible bismuth-based catalyst presents the structure of bismuth oxycarbonate at low voltage and the structure of metallic bismuth at high voltage. After removing the applied voltage, the metallic bismuth will spontaneously reconstruct into bismuth oxycarbonate after being immersed in the electrochemical carbon dioxide reduction reaction cell for more than 5 minutes. By using the reaction voltage to control the structural composition of the catalyst, the catalyst can have the advantages of both metallic bismuth and bismuth oxycarbonate, and has excellent electrochemical carbon dioxide reduction performance at both low and high potentials. Therefore, compared with commercial metallic bismuth and commercial bismuth oxycarbonate, this structurally reversible bismuth-based catalyst can realize efficient electrochemical carbon dioxide reduction in a wider voltage range and obtain good formic acid conversion Faraday efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The following are scanning electron microscope photos of the bismuth-based catalysts prepared in Examples 1-2 and Comparative Examples 1-2.

[0036] Figure 2 The X-ray diffraction patterns of the bismuth-based catalysts prepared in Examples 1-2 and Comparative Examples 1-2 are shown.

[0037] Figure 3 3 is the X-ray diffraction pattern of the sample under different voltage conditions in Example 3.

[0038] Figure 4This is the in-situ Raman spectrum of the sample under different voltage conditions in Example 3.

[0039] Figure 5 The following are the XRD patterns of commercial bismuth carbonate and commercial metallic bismuth.

[0040] Figure 6 The current density-potential diagrams of the bismuth-based catalysts prepared in Examples 1-2 and Comparative Examples 1-2 during electrochemical carbon dioxide reduction.

[0041] Figure 7 The current density-potential diagram of the bismuth-based catalyst prepared in Example 1, commercial bismuth oxycarbonate and commercial metallic bismuth during electrochemical carbon dioxide reduction.

[0042] Figure 8 The formic acid Faraday efficiency of the bismuth-based catalyst prepared in Example 1, commercial bismuth oxycarbonate and commercial metallic bismuth during electrochemical carbon dioxide reduction. DETAILED DESCRIPTION

[0043] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0044] Example 1

[0045] A bismuth-based catalyst (named BBN-140°C) is prepared in the following steps:

[0046] (1) Synthesis of bismuth basic nitrate (BBN) precursor: First, 0.1 g of bismuth nitrate pentahydrate and 1 mL of ammonia water were dissolved in 40 mL of benzyl alcohol and 40 mL of ethylene glycol, and then the solution was placed in a reactor and solvothermal at 140°C for 24 hours. The sample was then centrifuged at 3500 rpm and washed with ethanol. The centrifugation and washing process was repeated three times, and then the sample was placed in a 60°C oven for drying to obtain a bismuth basic nitrate precursor.

[0047] (2) Electrochemical reconstruction to form a bismuth-based catalyst: The bismuth basic nitrate precursor powder obtained in step (1) was calcined at 140° C. in an air atmosphere for 5 hours to obtain a bismuth-based catalyst BBN-140° C.

[0048] Example 2

[0049] A bismuth-based catalyst (named BBN-90°C) is different from Example 1 in that in step (2) of this example, the calcination temperature is 90°C, and the remaining preparation steps are the same as Example 1.

[0050] Example 3

[0051] A bismuth-based catalyst, the specific preparation steps are as follows:

[0052] Take the bismuth-based catalyst BBN-140℃ prepared in Example 1, use 5wt% perfluorosulfonic acid solution to stick the bismuth-based catalyst BBN-140℃ on carbon paper as a working electrode, apply a voltage of -0.7V in a CO2-saturated 0.5mol / L potassium bicarbonate electrolyte for 1h, and basic bismuth nitrate can be converted into bismuth oxycarbonate; continue to apply a voltage of -1.2V to the bismuth oxycarbonate in a CO2-saturated 0.5mol / L potassium bicarbonate electrolyte for 1h, and bismuth oxycarbonate can be converted into metallic bismuth; remove the applied voltage, and continue to soak the metallic bismuth in the CO2-saturated 0.5mol / L potassium bicarbonate electrolyte, the metallic bismuth will spontaneously react with the CO2 in the solution and be converted back into bismuth oxycarbonate.

[0053] Comparative Example 1

[0054] A bismuth-based catalyst (named BBN) is different from Example 1 in that step (2) is omitted in this example, and the remaining preparation steps are the same as those in Example 1.

[0055] Comparative Example 2

[0056] A bismuth-based catalyst (named BBN-190°C) is different from Example 1 in that in step (2) of this example, the calcination temperature is 190°C, and the remaining preparation steps are the same as Example 1.

[0057] Characterization Tests:

[0058] (1) Characterization of morphology and crystal structure of samples obtained at different calcination temperatures

[0059] Figure 1 The scanning electron microscope photos of the bismuth-based catalysts prepared in Examples 1-2 and Comparative Examples 1-2, wherein a is Comparative Example 1, b is Example 2, c is Example 1, and d is Comparative Example 2. It can be clearly seen from the figure that without calcination ( Figure 1 a) or calcined at 90°C ( Figure 1 In the case of b), the sample presents the morphology of nanoparticles with a diameter of about 100nm. After calcination at 140℃, the morphology of the sample changes significantly from nanoparticles to nanosheets ( Figure 1c). Compared with nanoparticles, nanosheets have a higher specific surface area and can expose more active sites. Further increasing the calcination temperature to 190°C, although the nanosheet morphology can be retained, the sample morphology is not as uniform as when calcined at 140°C ( Figure 1 d).

[0060] Figure 2 The X-ray diffraction (XRD) patterns of the bismuth-based catalysts prepared in Examples 1-2 and Comparative Examples 1-2 are shown in the figure. As can be seen from the figure, the XRD peaks of the samples without calcination, calcined at 90°C and calcined at 140°C match well with basic bismuth nitrate Bi6O5(OH)3(NO3)5·2H2O (standard card number: 54-0627), proving that the main component of the calcined product obtained is basic bismuth nitrate. Further increasing the calcination temperature to 190°C, the XRD peak of the sample changes significantly and matches well with β-Bi2O3 (standard card number: 27-0050). The XRD data show that if the calcination temperature is too high, basic bismuth nitrate cannot be obtained, but bismuth oxide will be formed.

[0061] (2) Crystal structure characterization of samples under different voltage conditions

[0062] Figure 3 The X-ray diffraction (XRD) patterns of the samples under different voltage conditions in Example 3, where a is the sample without voltage, b is the sample after applying -0.7V voltage, and c is the sample after applying -1.2V voltage. The figure shows the XRD spectrum of the calcined product sample loaded on carbon paper. Although the diffraction peak of the carbon paper itself is strong, the main peak of bismuth subnitrate at 11.6° is still clearly visible ( Figure 3 a). When the basic bismuth nitrate was treated with -0.7V-1h, its XRD spectrum changed significantly, and its diffraction peak matched well with bismuth oxycarbonate (standard card number: 41-1448) ( Figure 3 b), proving that its composition has changed from basic bismuth nitrate to bismuth oxycarbonate. When the bismuth-based catalyst is further treated with -1.2V-1h, its composition changes again, and its diffraction peak matches well with metallic bismuth (standard card number: 44-1246) ( Figure 3 c), proving that its composition changes from bismuth oxycarbonate to metallic bismuth.

[0063] (3) In situ Raman spectroscopy characterization of samples under different voltage conditions

[0064] In order to better explore the structural changes of the bismuth-based catalyst samples prepared in the example under different voltage conditions, in-situ Raman spectroscopy tests were carried out. The samples were treated in sequence from low to high voltages. Each voltage was treated for 1 hour and its Raman spectrum was measured. Figure 4] are the in-situ Raman spectra of the samples under different voltage conditions in Example 3, wherein a is the first test and b is the second test.

[0065] like Figure 4 As shown in a, when no voltage is applied initially, the sample is at about 120 cm -1 and 315cm -1 The position of the Bi-O bond peak is about 400 cm -1 The position of the Bi-OH bond peak is about 470 cm -1 The positions show characteristic peaks of bismuth basic nitrate (BBN), which correspond to the chemical structure of BBN (Bi6O5(OH)3(NO3)5·2H2O).

[0066] Then different voltages were applied to the surface of the material. As the voltage increased, the characteristic peak of bismuth subnitrate disappeared at -0.1 to -0.8 V, and the peak at about 160 cm -1 A new peak appears at the position of , which is the characteristic peak of bismuth oxycarbonate (BOC), proving that the material has been transformed from BBN to BOC.

[0067] As the voltage increases further, at -0.9 V, at about 94 cm -1 A new peak appears at the position of the electrode, which corresponds to the characteristic peak of metal bismuth (Bi). As the voltage increases further, the characteristic peak of BOC disappears, while the characteristic peak of metal bismuth remains unchanged, proving that the material has been transformed from BOC to metal bismuth.

[0068] When the voltage is removed, the metallic bismuth is rapidly oxidized in the CO2-saturated potassium bicarbonate solution. After 5 minutes, the characteristic peak of the metallic bismuth in its Raman spectrum disappears, and the peak at about 160 cm -1 The characteristic peak of BOC reappeared at the position of , proving that the material can spontaneously change from metallic bismuth to BOC.

[0069] In order to verify whether the sample can be converted from BOC to metallic bismuth again and then back to BOC, a second in-situ Raman test was performed on the sample. Figure 4 As shown in b, the second test and the first test showed a similar structural change trend. Under low voltage (-0.1~-0.8V), the material maintained the structure of BOC; under high voltage (-0.9~-1.5V), the material maintained the structure of metallic bismuth; when the voltage was removed, the metallic bismuth could turn back into BOC.

[0070] The above in situ Raman test results prove that by controlling the voltage conditions, the bismuth-based catalyst can spontaneously present the structures of BOC and metallic bismuth respectively.

[0071] (4) Characterization of electrochemical CO2 reduction performance

[0072] The catalyst samples prepared in the examples and comparative examples were subjected to electrochemical carbon dioxide reduction tests, and commercial bismuth oxycarbonate and commercial metallic bismuth (both commercial catalysts were purchased from Sigma-Aldrich) were also subjected to electrochemical carbon dioxide reduction tests. Figure 5 The XRD patterns of commercial bismuth oxycarbonate and commercial metallic bismuth correspond to the standard PDF cards of bismuth oxycarbonate (standard card number: 41-1448) and metallic bismuth (standard card number: 44-1246), respectively.

[0073] The electrochemical workstation model used for the electrochemical test is Chenhua CHI660E. The electrochemical test adopts a three-electrode system. The carbon paper coated with the catalyst is used as the working electrode, and is placed on one side of the H-shaped electrolytic cell together with the calomel electrode as the reference electrode. The ruthenium iridium titanium electrode as the counter electrode is placed on the other side of the H-shaped electrolytic cell. The H-shaped electrolytic cell is separated by a proton exchange membrane in the middle, and the electrolyte is a 0.5 mol / L potassium bicarbonate solution saturated with CO2. All potentials in the embodiments of the present invention have been converted relative to the reversible hydrogen electrode (RHE), and the conversion relationship from the calomel electrode to the RHE is: E RHE =E 甘汞电极 +(0.197+0.059×pH) V. The electrochemical carbon dioxide reduction test is a constant potential test at different potentials, the potential application time is 1h, the potential range is set to -0.4 to -1.5V, and then the composition and content of the electrolyte after the test are analyzed by liquid chromatography.

[0074] First, the electrochemical carbon dioxide reduction performance of the bismuth-based catalysts prepared in Examples 1-2 and Comparative Examples 1-2 was compared. Figure 6 The current density-potential diagram of the bismuth-based catalysts prepared in Examples 1-2 and Comparative Examples 1-2 during electrochemical carbon dioxide reduction. As can be seen from the figure, compared with Comparative Examples 1-2, Examples 1-2 have higher current density at the same potential. Further, compared with Example 2, BBN-140℃ prepared in Example 1 has a higher current density, proving that BBN-140℃ has higher CO2 reduction performance, which is attributed to the nanosheet morphology obtained under 140℃ calcination conditions.

[0075] Furthermore, the electrochemical carbon dioxide reduction performance of the bismuth-based catalyst prepared in Example 1 was compared with that of commercial bismuth oxycarbonate and commercial metallic bismuth. Figure 7The current density-potential diagram of the bismuth-based catalyst, commercial bismuth oxycarbonate and commercial metallic bismuth prepared in Example 1 during electrochemical carbon dioxide reduction. As can be seen from the figure, the BBN-140°C material prepared in Example 1 exhibits a higher current density at different potentials than commercial bismuth oxycarbonate and commercial metallic bismuth, proving that its catalytic activity is higher than that of commercial bismuth oxycarbonate and commercial metallic bismuth.

[0076] Furthermore, the selectivity of the three catalysts towards formic acid was tested. Figure 8 The formic acid Faraday efficiency of the bismuth-based catalyst, commercial bismuth oxycarbonate and commercial metallic bismuth prepared in Example 1 during electrochemical carbon dioxide reduction. As can be seen from the figure, the materials prepared in Example 1 all exhibited high Faraday efficiencies at -0.5 to -1.4V (90.6%, 91.5%, 92.9%, 91.9%, 92.8%, 92.9%, 92.8%, 95.9%, 93.7% and 91.9%, respectively), which are much higher than commercial bismuth oxycarbonate and commercial metallic bismuth. On the other hand, at low potentials (-0.4 to -0.8V), the formic acid Faraday efficiency of commercial bismuth oxycarbonate is higher than that of commercial metallic bismuth; at high potentials (-0.9 to -1.3V), the formic acid Faraday efficiency of commercial metallic bismuth is higher than that of commercial bismuth oxycarbonate. This shows that bismuth oxycarbonate is more active at low potentials, while metallic bismuth performs better at high potentials. The structurally reversible bismuth-based catalyst prepared in the embodiment of the present invention presents the structure of bismuth oxycarbonate at low potential and the structure of metallic bismuth at high potential. Therefore, it has high formic acid selectivity both at low potential and high potential. The formic acid selectivity is higher than 90% within the potential range of 1V, and it has excellent electrochemical carbon dioxide reduction to produce formic acid performance.

[0077] In summary, in the embodiments of the present invention, a bismuth-based catalyst is prepared by adopting specific raw materials and specific preparation conditions, wherein ammonia water can be complexed with bismuth nitrate to make it undergo a solvothermal reaction in a specific alcohol solvent, and the unique bismuth-based catalyst of the present invention can be synthesized, which has the characteristics of variable and reversible chemical composition, and thus can achieve electrochemical carbon dioxide reduction within a wider voltage range. Compared with commercial metallic bismuth and commercial bismuth oxycarbonate, this structurally reversible bismuth-based catalyst can achieve efficient electrochemical carbon dioxide reduction within a wider voltage range, and can maintain a formic acid conversion Faraday efficiency of more than 90% within a voltage range of -0.5 to -1.4 V, and thus has good application prospects in industrial large-scale electrochemical carbon dioxide reduction.

Claims

1. A method for preparing a bismuth-based catalyst, characterized in that: The following steps are involved: Bismuth nitrate, ammonia water, ethylene glycol and benzyl alcohol are mixed and subjected to solvent thermal reaction to obtain a basic bismuth nitrate precursor; the basic bismuth nitrate precursor is calcined to obtain the bismuth-based catalyst; the calcination temperature is less than 190°C.

2. The preparation method according to claim 1, characterized in that: The dosage ratio of the bismuth nitrate to the ammonia water is 1g: (5~20)mL; And / or, the usage ratio of the bismuth nitrate to the ethylene glycol is 1 g: (200-800) mL; And / or, the usage ratio of the bismuth nitrate to the benzyl alcohol is 1 g: (200-800) mL.

3. The preparation method according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 100 to 180°C; And / or, the solvent thermal reaction time is 10 to 40 hours.

4. The preparation method according to claim 1, characterized in that: The calcination temperature is 50 to 180°C; And / or, the calcination time is 3 to 7 hours; And / or, the calcination is performed under air atmosphere.

5. The preparation method according to claim 1, characterized in that: After the calcination, the method further comprises the following steps: subjecting the calcined product obtained by the calcination to an electrochemical reduction reaction with a solution containing carbon dioxide under an applied voltage to obtain the bismuth-based catalyst.

6. The preparation method according to claim 5, characterized in that: The magnitude of the applied voltage is 0.2-2V.

7. A bismuth-based catalyst obtained by the preparation method according to any one of claims 1 to 6.

8. The bismuth-based catalyst according to claim 7, characterized in that The bismuth-based catalyst changes its chemical composition in a solution containing carbon dioxide with different applied voltages; under low applied voltage or no applied voltage, the chemical composition of the bismuth-based catalyst is basic bismuth nitrate or bismuth oxycarbonate; under high applied voltage, the chemical composition of the bismuth-based catalyst is elemental bismuth.

9. The bismuth-based catalyst according to claim 8, characterized in that The low applied voltage has a magnitude range of greater than 0V and less than or equal to 0.9V; the high applied voltage has a magnitude range of greater than 0.9V and less than or equal to 2V.

10. Use of the bismuth-based catalyst according to any one of claims 7 to 9 in electrochemical carbon dioxide reduction.